Tetraalkylammonium-based dicationic ionic liquids (ILs) for CO2 capture - Kulkarni, Prashant S.; Ranjane, Prathamesh; Mishra, Karun; Sundararajan, Swati; Kamble, Sanjay (New Journal of Chemistry, 2023)
This investigation includes the synthesis and characterization of a new series of ionic liquids (ILs) based on the tetraalkylammonium dication for the absorption of CO2, a step towards the development of more efficient and sustainable technologies. It was possible to synthesize amine-substituted PEG diacrylate by modifying poly(ethylene glycol) (PEG), which was then quaternized with 1-bromopentane to produce the IL PDBr. The other IL products, PDNTf2, PDBF4 and PDPF6, were synthesized via the metathesis of PDBr with the appropriate salt. The synthesized products were characterized using various techniques, such as FTIR, H-1 and C-13 NMR, elemental analysis, and density and viscosity meters, and evaluated as potential sorbents for CO2 capture. DSC and TGA were used to examine the thermal properties of the ILs. As observed from their thermal degradation behavior, the ILs exhibited two-stage disintegration with thermal stability up to 150 & DEG;C. The pressure drop method was used to study the sorption capacity of the ILs towards CO2. The sorption investigation showed that when the pressure is increased, the CO2 absorption increases. Equilibrium is reached in 40 minutes, demonstrating a rapid absorption rate. The IL with the [BF4](-) anion (PDBF4) demonstrated a maximum sorption capacity of 0.577 mole fraction of CO2, and can be regenerated and reused efficiently with less than 0.5% variation from its original absorption capacity. The CO2 absorption capacity for the ILs with other anions follows the trend: Br & AP; NTf2 < PF6 < BF4. This work shows that tetraalkylammonium-based dicationic ILs are adaptable, making them a suitable material for many applications, including sustainable CO2 capture technology.